A fire risk assessment method for high-capacity battery packs using interquartile range filter. (June 2022) - Cho, Inho; Park, Seongyun; Kim, Jonghoon
Abstract: Lithium-ion batteries are chosen as the most suitable device for energy storage system (ESS) due to their high energy density. However, lithium-ion batteries have high chemical reactivity, which increase the fire risk of products using them. Accordingly, various studies have been conducted to prevent lithium-ion battery-fire accidents but the main purpose of the conventional studies was to prevent the spread of fire after it started rather than predicting the risk of fire. Thus, there is a limit to reducing the maintenance time and cost of ESS. In this paper, a new method for real-time monitoring of the fire risk during operation of the battery pack is proposed. It combines with the electrochemical theory while using the real-time data from the electrically measured factors to select the aged cells. Also, a method of assessing the fire risk of battery packs by applying the interquartile range (IQR) filter to real-time data obtained from the electrically measured factors of battery packs is proposed. The feasibility of the proposed method is verified by the experiment using the specifications of the high-capacity battery packs used for railway vehicles. Highlights: ESSs with lithium-ion batteries have high risk of fire. The process of thermal of lithium-ion batteries is analyzed. The electrical factors applicable to determining the risk of fire in an ESS are derived. Fire risk assessment method using IQR filter is proposed. The feasibility of the proposed method is verified with a hybrid powered railway vehicle specifications.